Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.52965/001c.24978
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Postoperative Opioid Use and Alternative Pain Control Following Spine Surgery

Abstract: Opioids are commonly prescribed postoperatively for pain control, especially in spine surgery. Not only does this pose concerns for potential abuse, but it also has been shown to worsen certain outcomes. Risk factors for increased use include preoperative opioid use, female sex, psychiatric diagnoses, and drug and alcohol use. Over the past few decades, there have been increasing efforts mostly spearheaded by governmental agencies to decrease postoperative opioid use via opioid prescription limitation laws reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 97 publications
2
3
0
Order By: Relevance
“…Patients enrolled in the ERAS protocol, denoted as ERAS+, exhibited diminished rates of opioid utilization at baseline, in accordance with the protocol’s accentuation on preoperative counseling and educational interventions focused on pain management. This observation holds particular relevance within the domain of spine surgery and the inherent risks of chronic pain and postoperative opioid dependency concerns 22 . The present study also elucidates the significance of multimodal analgesia embedded within ERAS protocols, aligning with antecedent investigations that have expounded upon its efficacy in the context of lumbar spine fusion procedures 23 …”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Patients enrolled in the ERAS protocol, denoted as ERAS+, exhibited diminished rates of opioid utilization at baseline, in accordance with the protocol’s accentuation on preoperative counseling and educational interventions focused on pain management. This observation holds particular relevance within the domain of spine surgery and the inherent risks of chronic pain and postoperative opioid dependency concerns 22 . The present study also elucidates the significance of multimodal analgesia embedded within ERAS protocols, aligning with antecedent investigations that have expounded upon its efficacy in the context of lumbar spine fusion procedures 23 …”
Section: Discussionsupporting
confidence: 56%
“…This observation holds particular relevance within the domain of spine surgery and the inherent risks of chronic pain and postoperative opioid dependency concerns. 22 The present study also elucidates the significance of multimodal analgesia embedded within ERAS protocols, aligning with antecedent investigations that have expounded upon its efficacy in the context of lumbar spine fusion procedures. 23 In terms of the economic dimensions of ERAS implementation in CD surgery, reduced hospital length of stay (LOS) and increased rates of home discharge for ERAS+ patients directly contribute to lower health care utilization costs.…”
Section: Discussionsupporting
confidence: 53%
“…d’Astorg et al 11 retrospectively studied the effect that their ERAS protocol had on pain and LOS and found that both pain and hospital LOS were decreased in the ERAS group. The comprehensive pain management approach of ERAS, including preoperative analgesics, regional nerve blocks, and judicious opioid use, serves to minimize postoperative pain and reduce opioid consumption, facilitating earlier ambulation and mobility, and supporting home-based care transition 2,12 . In addition, structured preoperative counseling, expectation management, and discharge planning also likely played a significant role in facilitating discharge to home in our study, a critical component of the late cohort’s ERAS protocol.…”
Section: Discussionmentioning
confidence: 95%
“…This association highlights the importance of thorough preoperative assessments, where clinicians must weigh the necessity of continued opioid use against potential alternatives for pain management. Preoperative opioid utilization has also been shown to increase rates of one-year reoperations, emergency department visits, epidural and facet joint injections, and wound complications and hinder patient-reported outcomes [ 3 , 11 , 16 ]. McCurdy et al found that preoperative opioid use correlated with worse PROMIS scores two years postoperatively, including pain interference and pain intensity, influencing outcomes and the possibility of increased postoperative opioid use [ 17 ].…”
Section: Discussionmentioning
confidence: 99%